Beclin-1 is involved in the regulation of antimicrobial peptides expression in Chinese mitten crab Eriocheir sinensis. Issue 89 (June 2019) - Yang, Wen; Liu, Chao; Xu, Qingsong; Qu, Chen; Sun, Jiejie; Huang, Shu; Kong, Ning; Lv, Xiaojing; Liu, Zhaoqun; Wang, Lingling; Song, Linsheng
Abstract: Beclin-1, the mammalian ortholog of yeast Atg6, plays essential roles in the regulation of various processes, including autophagy, apoptosis, embryonic development and immune responses in vertebrates. However, the information about Beclin-1 in invertebrates especially in crustaceans is still very limited. In the present study, a novel Beclin-1 (designated as Es Beclin-1) was identified from Chinese mitten crab Eriocheir sinensis . The open reading frame of Es Beclin-1 cDNA was of 1, 275 bp, encoding a typical APG6 domain. The deduced amino acid sequence of Es Beclin-1 shared high similarity ranging from 42.9% to 63.6% with the previously identified Beclins. In the phylogenetic tree, Es Beclin-1 was firstly clustered with Drosophila melanogaster Atg6 and then assigned into the branch of invertebrate Beclin-1. The mRNA transcripts of Es Beclin-1 were highly expressed in hepatopancreas, hemocytes and gill. After lipopolysaccharide (LPS) and Aeromonas hydrophila stimulations, the relative mRNA expression of Es Beclin-1 in hemocytes was significantly increased from 3 to 24 h with the peak level of 4.70-fold ( p < 0.01) and 2.91-fold ( p < 0.01) at 6 h, respectively. Es Beclin-1 protein was diffusely distributed in the cytoplasm of crab hemocytes under normal conditions, whereas it displayed predominantly punctuate distribution after LPS stimulation. After Es Beclin-1 was interfered with specific Es Beclin-1-dsRNA, the mRNA transcripts of some antimicrobial peptides, including Es ALF2, Es LYZ, Es Crus and Es Crus2 in crab hemocytes were significantly decreased at 6 h post LPS stimulation. These results implicated that Es Beclin-1 played a role in regulating the antimicrobial peptides expressions in the immune responses of E. sinensis . Highlights: Es Beclin-1 was a homolog of vertebrate Beclin-1 in Eriocheir sinensis. Es Beclin-1 mRNA transcripts increased post the stimulations of LPS and A. hydrophila. Es Beclin-1 aggregated and punctuated in the cytoplasm post LPS stimulation. Es Beclin-1 regulated the expressions of Es ALF2, Es LYZ, Es Crus, Es Crus2 post LPS stimulation.